Análise e design eficiente para a geração dos elementos sintáticos residuais segundo o padrão VVC - (:unkn) unknown (Universidade Federal do Pampa, 2026)
The increasing consumption of video content, driven by streaming platforms and social media, demands the development of efficient data compression and transmission techniques. In this context, the Versatile Video Coding (VVC/H.266) standard stands out, offering compression rates up to 50% higher than its predecessor, HEVC. However, this efficiency results in a considerable increase in computational complexity, slowing down encoding on general-purpose devices and making real-time applications unfeasible without dedicated hardware. The main objective of this work is to perform a detailed statistical analysis of the Residual Syntax Elements (RSEs) in VVC for the Transform-base and Transform-skip modes and, based on this analysis, to propose and implement dedicated hardware architectures for their generation. The statistical analysis, performed using the VVC Test Model (VTM) across various test sequences and quantization parameters (QP), confirmed that RSEs are predominant or make a significant contribution to the entropy coding (CABAC) input data, being crucial for the encoder’s throughput. The results also evidenced that, while the Transform mode is predominant, the Transform-skip mode can reach up to 26.53% usage in certain sequences. Given that RSEs are predominant, the need for a dedicated hardware architecture for generating these elements is evident. The proposed architectures were described in VHDL and synthesized using the TSMC 40 nm technology node. Operating at a frequency of 1 GHz, the complete system consumed only 3.23 mW of power and occupied an area of 11.8 K gates, while at 1.5 GHz it occupied 15.5 K gates and consumed 6.11 mW of power. Compared to similar works in the literature targeting VVC, the developed solution stood out by achieving area savings from 70.2% to 77.3% and dissipating less than half the power at 1 GHz.
Keywords: Codificação de vídeo; VVC; Elementos sintáticos residuais; Transformada; Transform-skip; Codificação de entropia; Video coding; Residual syntax elements; Hardware architecture; Transform; Entropy coding; CIENCIAS EXATAS E DA TERRA